Exploring the talent training mode of“cybersecurity doctor” - Xingshu CHEN; Haizhou WANG; Wenxian WANG; Ping YANG; Shuhua RUAN (网络与信息安全学报)
The competition for cyber security is ultimately the competition of talents.Countries around the world have placed cyber security talents at the national strategic level.As a new interdisciplinary subject,the intension and extension of cyber security discipline is still evolving and developing.So far,it lacks a talent training mode and evaluation mechanism suitable for the characteristics of cyber security talents.Based on years of teaching research,with reference to the existing advanced training models and evaluation mechanisms in foreign countries,combined with the actual situation in China,an innovative training mode of “cybersecurity doctor” suitable for the characteristics of cybersecurity disciplines is proposed.It covers the whole life cycle of undergraduate training.With problem orientation,students are trained to find security problems and solve them in cyberspace.Universities,industry and research institutions are closely interacting.Furthermore,it improves students' knowledge,skills and practical application ability,develops interest and ability to explore the latest advanced and core technologies,improves the quality of our teachers and education,and also helps enterprises select outstanding talents,enhance their research and development capabilities and market competitiveness.In the end,the two sides will achieve synergy and innovation,complement each other,and achieve a comprehensive win-win situation,and promote the cultivation of cyber security talents and the development of disciplines.